Oral hygiene practices in pediatric intensive care units: a scoping review - Fabiana Bucholdz Teixeira Alves; Marcos Cezar Pomini; Paulo Sérgio da Silva Santos; Gabriela Moura Chicrala; Luiz Alberto Valente Soares Júnior (Revista de Enfermagem da UFPI)
Objective: To explore and map the literature on oral hygiene (OH) practices in pediatric patients admitted to Pediatric Intensive Care Units (PICU). Methods: The Arksey and O’Malley’s five-stage methodological framework for scoping reviews was conducted using Pubmed, Bireme, Scopus, Web of Science and Cochrane Library databases. Clinical trials reporting OH practices in PICU and published in English language were included. Non-interventional studies, case reports and studies with neonates, adolescents or adults were excluded from the review. Results: The 11 included studies indicate that OH has been integrated into protocols for the prevention of ventilator-associated pneumonia (VAP) or into prevention bundles. The most common agent used for OH in mechanically ventilated children was 0.12% chlorhexidine. There is not enough evidence to support a safe and uniform protocol for OH in children admitted to PICU. Conclusion: A gap regarding OH in non-ventilated children was found in the literature. Further studies are needed to support the development of a uniform, safe, effective and evidence-based OH protocol for children in PICU.